Optimalkan Kinerja Pegawai; Peran Lingkungan Kerja Fisik dan Pengembangan Karir - Nurul Maghfirah; Felix Chandra (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
This study aims to evaluate the impact of work environment and career development on employee performance at the BPJS Kesehatan Ambon Branch Office. The population involved in this study were 35 employees at BPJS Kesehatan Ambon Branch, who were randomly selected as the research sample. The tool used to collect data is a questionnaire designed to extract information about the variables of Work Environment, Career Development, and Employee Performance. Validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression analysis, t-test, f-test, and coefficient of determination were used to analyze the data. -The findings show that employee performance and work environment at BPJS Ambon Branch have a positive and significant relationship. In addition, at the BPJS Ambon Branch office, there is a noteworthy and positive correlation between employee performance and Career Development. In general, the Ambon Branch BPJS office sees a simultaneous influence between employee performance and work environment. -The findings show that the physical work environment contributes 47.7% to employee performance based on the coefficient of determination (R2).